2020
DOI: 10.1021/acsabm.0c00476
|View full text |Cite
|
Sign up to set email alerts
|

High-Quality Inorganic Red Pigment Prepared by Aluminum Deposition on Biogenous Iron Oxide Sheaths

Abstract: Naturally occurring tubular iron oxides produced by aquatic bacteria in Leptothrix spp. are promising raw materials for hematite-based red pigments because of the higher heat resistance as compared with chemically synthesized hematite compounds. Here, we report iron oxide red pigments prepared through an additive deposition of aluminum on culture-based biogenous iron oxide (cBIOX) sheaths using an artificial culture system of L. cholodnii strain OUMS1. The heat-treated Al-containing cBIOXs exhibited elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that the inclusion of Al in the chemically synthesized hematite-based pigments produced yellowish-red hues 22 − 24 and that the additive deposition of Al in BIOX-derived pigments resulted in an increased yellowish intensity. 21 Using a two-step method, 19 we have prepared highly enriched Al-containing cBIOX sheaths by the addition of 10 mM AlCl 3 solution over various concentrations of ZnSO 4 . Tube-shaped sheaths of cBIOX were successfully obtained at low concentrations of ZnSO 4 (≤10 mM), while an excess of sulfate ions might hinder the formation of cBIOX.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that the inclusion of Al in the chemically synthesized hematite-based pigments produced yellowish-red hues 22 − 24 and that the additive deposition of Al in BIOX-derived pigments resulted in an increased yellowish intensity. 21 Using a two-step method, 19 we have prepared highly enriched Al-containing cBIOX sheaths by the addition of 10 mM AlCl 3 solution over various concentrations of ZnSO 4 . Tube-shaped sheaths of cBIOX were successfully obtained at low concentrations of ZnSO 4 (≤10 mM), while an excess of sulfate ions might hinder the formation of cBIOX.…”
Section: Resultsmentioning
confidence: 99%
“…Color tone values (CIE L * a * b *) of heat-treated samples were measured by spectrophotometry (CM- 2600d, Konica–Minolta Inc., Tokyo, Japan) using a CIE standard illuminant D65 and SCI mode as previously described. 21 Powder samples were loaded into cylindrical pits (φ 8 mm, 0.5 mm in depth) on glass holders using a plastic film to flatten the compacted powders’ surface for accurate measurements. A commercially available iron oxide pigment MC-55 (Morishita Bengara Kogyo Co., Ltd., Mie, Japan) was used as the color reference.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The need for reliable information on the structural and functional characteristics of nanosized materials produced by Leptothrix bacteria has grown in recent years [1][2][3]. The microaerophilic iron-oxidizing βproteobacteria from the genus Leptothrix are of great interest because during their growth they produce extracellular formations containing iron oxides and oxyhydroxides.…”
Section: Introductionmentioning
confidence: 99%